Birth, Rise, Decline and Revival of Home Hemodialysis - French experience - Alain Meyrier (RDPLF, 2018)
The first publication in 1960 on maintenance hemodialysis was followed in 1963 by some reports on dialysis in the home. The introduction of proportioning pumps and concentrated electrolyte solutions led to developing single-patient machines and safety devices that made home hemodialysis possible.  It was demonstrated in 1964 that home hemodialysis can be done overnight, unattended. This led to a steady rise in the number of patients treated at home. The percentage in France was ≈20% by the end of the seventies, out of a total of  ≈ 6 000.  The decline began when Public Health authorities authorized a program of ''limited - care'' units.  A loophole in the regulations led to a massive transfer of patients to these units and a rapid decline of home HD. The revival can be dated to 2012 with the development of disposable dialysate bags that make low flow daily home HD feasible. Efficacy and tolerability are such that the total number of patients treated at home rose from 307 in 2014 to 374 in 2016, owing to those on daily hemodialysis -  an increase from 55 in 2014 to 374 in 2016 and 448 by the end of 2018. Currently, ≈46 000 patients are hemodialyzed in France.   The % of those treated at home is very low but the trend is to a steady increase.